2009
DOI: 10.2355/tetsutohagane.95.710
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Global Demand for Iron Source by Estimation of In-use Steel Stock

Abstract: The Utility of Stock hypothesis, which assumes that the in-use stock of constructional material is a function of GDP, was formulated and the clear correlation between the world steel stock and the GDP led to the estimation that the world demand for iron ore (primary iron) depends not on the volume of GDP but on the variation of GDP, as already reported. In this study, the world steel stock in use is computed. Sensitivity analyses are conducted to show the effect of lower reliable data such as the usage period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…As already reported, 2) the relationship between the world steel stock in use and the world GDP shows two straight lines which is inflected in the year 1982 (Fig. 8).…”
Section: Case II (Length Of Regressionsupporting
confidence: 68%
See 4 more Smart Citations
“…As already reported, 2) the relationship between the world steel stock in use and the world GDP shows two straight lines which is inflected in the year 1982 (Fig. 8).…”
Section: Case II (Length Of Regressionsupporting
confidence: 68%
“…As already reported, [1][2][3] we have proposed the Utility of Stock hypothesis which assumes that an in-use stock of constructional material is a function of GDP and found a clear correlation between the world steel stock and the world GDP and also a clear correlation between the world production of crude steel and the world production of primary iron. It is concluded that it is significant to predict the world demand of iron source based on the guiding principle that the production of primary iron is a function of the variation of GDP and the production of crude steel is a function of the production of primary iron.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations